New Synonyms and Typification of Myrcia sect. Myrcia (Myrtaceae) - Santos, Leidiana L.; Athiê-Souza, Sarah M.; Lucas, Eve; Sales, Margareth Ferreira De (Phytotaxa, 2019)
Four new synonyms are here proposed for species of Myrcia sect. Myrcia: Myrcia brasiliae under M. lasiantha, M. pernambucensis under M. bergiana, M. recurvata under M. ovata, and M. sosias under M. undulata. Additionally, 42 lectotypifications for species of Myrcia sect. Myrcia are proposed herein.